Neutrophils in the era of immune checkpoint blockade. Issue 7 (22nd July 2021) - Faget, Julien; Peters, Solange; Quantin, Xavier; Meylan, Etienne; Bonnefoy, Nathalie
Abstract : The immune checkpoint blockade-based immunotherapies are revolutionizing cancer management. Tumor-associated neutrophils (TANs) were recently highlighted to have a pivotal role in modulating the tumor microenvironment and the antitumor immune response. However, these cells were largely ignored during the development of therapies based on programmed cell death receptor or ligand-1 and cytotoxic T lymphocyte antigen-4 immune checkpoint inhibitors (ICIs). Latest evidences of neutrophil functional diversity in tumor raised many questions and suggest that targeting these cells can offer new treatment opportunities in the context of ICI development. Here, we summarized key information on TAN origin, function, and plasticity that should be considered when developing ICIs and provide a detailed review of the ongoing clinical trials that combine ICIs and a second compound that might affect or be affected by TANs. This review article synthetizes important notions from the literature demonstrating that: (1) Cancer development associates with a profound alteration of neutrophil biogenesis and function that can predict and interfere with the response to ICIs, (2) Neutrophil infiltration in tumor is associated with key features of resistance to ICIs, and (3) TANs play an important role in resistance to antiangiogenic drugs reducing their clinical benefit when used in combination with ICIs. Finally, exploring the clinical/translational aspects of neutrophil impact on the response to ICIs offers the opportunity to propose new translational research avenues to better understand TAN biology and treat patients.